Memorias y recomposiciones familiares - Segalen , Martine (Revista de Antropología Social, 2009)
Based on a series of interviews from selected informants belonging to a wide three-generation survey, this paper questions the specificity of memories in recomposed families. Social contrasts between the three generations are added to familial contrasts linked to separations, divorces and recomposition of couples. Starting with the anthropological analysis of contemporary memorial facts, the analysis reveals that memories are constructed during childhood, within the relationship with grandparents, itself dependant on the way the divorce and recomposition of the couple developed. Whatever the type of family, memory and remembrances processes appear to be singular reconstructions where each individual chooses the material necessary to arrange his specific memory, within the framework of a new family spirit.